2016
DOI: 10.1093/nar/gkw559
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of eIF5 or its protein mimic 5MP perturbs eIF2 function and inducesATF4translation through delayed re-initiation

Abstract: ATF4 is a pro-oncogenic transcription factor whose translation is activated by eIF2 phosphorylation through delayed re-initiation involving two uORFs in the mRNA leader. However, in yeast, the effect of eIF2 phosphorylation can be mimicked by eIF5 overexpression, which turns eIF5 into translational inhibitor, thereby promoting translation of GCN4, the yeast ATF4 equivalent. Furthermore, regulatory protein termed eIF5-mimic protein (5MP) can bind eIF2 and inhibit general translation. Here, we show that 5MP1 ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 30 publications
8
53
0
Order By: Relevance
“…Multiple factors and regulatory pathways converge to govern start codon selection, including EIF1 and EIF5. eIF1 (originally identified as Sui1) is known to increase the specificity of scanning 43S PICs for AUG start codons [58,103], while higher availability and abundance of eIF5 (originally Sui5) have been shown to decrease start codon fidelity [88,104,105]. Consistent with our prediction, we observed that EIF1 overexpression decreased RAN translation in a start codon-dependent manner, while over-expression of EIF5 did the opposite.…”
Section: A the Expression Of Plasmid-based Nl-3xf Reporters In Hek293supporting
confidence: 88%
See 1 more Smart Citation
“…Multiple factors and regulatory pathways converge to govern start codon selection, including EIF1 and EIF5. eIF1 (originally identified as Sui1) is known to increase the specificity of scanning 43S PICs for AUG start codons [58,103], while higher availability and abundance of eIF5 (originally Sui5) have been shown to decrease start codon fidelity [88,104,105]. Consistent with our prediction, we observed that EIF1 overexpression decreased RAN translation in a start codon-dependent manner, while over-expression of EIF5 did the opposite.…”
Section: A the Expression Of Plasmid-based Nl-3xf Reporters In Hek293supporting
confidence: 88%
“…Multiple factors and regulatory pathways converge to govern start codon selection, including EIF1 and EIF5 . eIF1 (originally identified as Sui1) is known to increase the specificity of scanning 43S PICs for AUG start codons , while higher availability and abundance of eIF5 (originally Sui5) have been shown to decrease start codon fidelity .…”
Section: Discussionmentioning
confidence: 99%
“…We have relied on past biochemical studies to inform our hypothesis that uORFs that do not allow for reinitiation after translation must be bypassed in order to de-repress the expression of the downstream CDS, as has been observed on GCN4 in yeast in a process termed "delayed reinitiation" (Mueller and Hinnebusch 1986, Abastado, Miller et al 1991, Hinnebusch 1997, Vattem and Wek 2004, Kozel, Thompson et al 2016). There are two determining cORFs upstream of the GCN4 CDS with the first showing persistent translation, and the second acting under normal conditions to preclude the scanning ribosome from reaching the CDS with a ternary complex for initiation (Hinnebusch 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of eIF5 in S. cerevisiae resulted in the inhibition of cell growth and a decrease in the rate of in vivo protein synthesis [159]. In yeast, eIF5 is able to mimic the effect of eIF2 phosphorylation, acting as a translational inhibitor and promoting translation of prooncogenic protein GCN4 (yeast equivalent of ATF4) [166,167]. When overexpressed in S. cerevisiae, eIF5 increases the levels of aN eIF2/eIF5 complex, which prevents eIF2B interaction and subsequently prevents ternary complex formation [167].…”
Section: Eif4fmentioning
confidence: 99%
“…5MP promotes expression of GADD34 (a downstream target of ATF4) in Tribolium castaneum [169]. Further, 5MP binds eIF2 to inhibit general translation and when overexpressed, it promotes ATF4 expression in fibrosarcoma [166,169]. ATF4 is expressed in hypoxic-and nutrientdeprived tumor regions, with functions in development, promoting metabolic homeostasis, and cancer cell proliferation [170].…”
Section: Eif4fmentioning
confidence: 99%